Advances in human glutamine-hydrolyzing synthetases and their therapeutic potential - Zhu, Wen; Nardone, Alanya J.; Pearce, Lucciano A. (Frontiers in Chemical Biology, 2024)
Bifunctional enzymes, characterized by their dual active sites, enable efficient chemical conversion and substrate channeling using elegant coupling mechanisms to coordinate the two active sites. In humans, several bifunctional enzymes synthesize de novo carbon-nitrogen bonds by hydrolyzing glutamine and ATP in distinct active sites. Notable examples include guanosine monophosphate synthetase, cytidine triphosphate synthetase, phosphoribosylformylglycinamidine synthase, asparagine synthetase, and nicotinamide adenine dinucleotide synthetase. A more complex example of multifunctional glutamine-hydrolyzing synthetases in humans is carbamoyl phosphate synthetase. These enzymes are crucial for the biosynthesis of amino acids, nucleic acids, and co-factors, thereby playing pivotal roles in human health. This review delineates recent progress in understanding the structural characteristics, regulatory mechanisms, and disease relevance of glutamine-hydrolyzing synthetases in humans. Insights into their catalysis and activity regulation offer potential pathways for developing novel therapeutics.